Intensity Modulated Radiotherapy (IMRT) Versus Helical Tomotherapy (HT) in Esophageal Cancer: A Comparative Analysis - Penumur, Manasa; Goswami, Smriti; Goswami, Bibhash Chandra; Choudhury, Diplu; Hassan, Fahim Arman; Bora, Ghritashee; Borah, Luri; Paul, Moumita; Baruah, Rheetwik; Saikia, Dimpal; Baruah, Kalyanjit Dutta (Asian Pacific Journal of Cancer Care, 2023)
Purpose/Objectives: Definitive chemoradiation is an accepted alternative treatment in the management of esophageal cancer in patients who are not candidates for surgery. The location of esophagus poses a challenge because of its close proximity to the critical organs. Various modern techniques of radiation planning offer the advantage of better dose conformality and increased sparing of organs at risk. This study aims to compare the dosimetric parameters of Intensity Modulated Radiotherapy (IMRT) and Helical Tomotherapy (HT) planning techniques in radical radiotherapy for esophageal cancer patients. Materials/Methods: A total of 38 patients of esophageal squamous cell carcinoma with clinical staging cT2-T4/N0-N2/M0 planned for definitive chemoradiation were enrolled from June 2021 till November 2022. CT simulation was done with intravenous and oral contrast, and contouring of tumor volumes and organs at risk were done according to RTOG contouring guidelines. All patients were planned for a total dose of 50.4Gy in 28 fractions. Radiation plans of IMRT and HT were generated for each patient. Dosimetric parameters of PTV D98, D2, Dmean, V95, V110, Homogeneity Index (HI) and Conformity Index (CI) were noted for both the plans. Organs at risk (OAR) parameters such as Lung (V20, V30, V5, Dmean), Heart (V25, V30, Dmean), Spinal Cord Dmax, Larynx (Dmax, Dmean) and Liver Dmean were noted. All parameters of the two different planning techniques were compared and analyzed using SPSS software v23 with paired t-test. Results: The coverage of the PTV in IMRT and HT was similar in terms of PTV V95 and PTV D98. The regions receiving more than 107% and 110% of the prescribed dose was significantly higher in IMRT compared to HT, on assessing V107, V110 and D2 (p=0.001). HI was similar in both the groups, but the CI was significantly better in HT compared to IMRT (0.9 ± 0.02 vs 1.03 ± 0.01; p=0.002). Doses to the lungs, heart and liver were similar between the two groups. IMRT had higher spinal cord (39.1 ± 3.2 vs 34.2 ± 5.5; p=0.001) and laryngeal dose (9.6 ± 5.5 vs 5.6 ± 3.7; p=0.009) compared to HT. Conclusion: HT offers better dose conformality and uniformity when compared to IMRT with lesser dose to spinal cord and larynx. As this is a dosimetric study, a larger sample size and patient follow up is essential for clinical correlation and assessment of benefit of different radiation modalities.